Stabilization control of the differential mobile robot using Lyapunov function and extended kalman filter - Tran, Thuan Hoang; Phung, Manh Duong; Van Nguyen, Thi Thanh; Tran, Quang Vinh (Vietnam Journal of Science and Technology, 2017)
This paper presents the design of a novel control model to navigate the differential mobile robot to reach the desired destination from an arbitrary initial pose. The designed model is divided into two stages: the state estimation and the stabilization control. In the state estimation, an extended Kalman filter is employed to optimally combine the information from the system dynamics and measurements. Two Lyapunov functions are constructed that allow a hybrid feedback control law to execute the robot movements. The asymptotical stability and robustness of the closed loop system are assured. Simulations and experiments are carried out to validate the effectiveness and applicability of the proposed approach.